Evaluation of the Physicochemical and Sensory Characteristics of Chicken Sausages Containing Different Types of Chicken Skin - Miwada, I Nyoman Sumerta; Susilo, Agus; Ariana, I Nyoman Tirta; Sriyani, Ni Luh Putu; Sumarmono, Juni (Jurnal Ilmu-Ilmu Peternakan, 2024)
This study aimed to determine the effects of adding chicken skin on the physicochemical and sensory characteristics of chicken sausages. Five sausage chicken formulations were produced with the following compositions: T1: Control (unfortified chicken skin); T2: fortified chicken skin 5%; T3: fortified chicken skin 10%; T4: fortified chicken skin15%; and T5: fortified chicken skin 20%. Our results revealed that the addition of chicken skin significantly (P<0.05) decreased the moisture content but significantly (P<0.05) increased the protein content in chicken sausages. Compared with the control, the sausages with chicken skin had significantly (p<0.05) greater pH values. The CIE L* value was significantly (p<0.05) greater than the CIE a* value compared with those of the control. Compared with the control condition, chicken skin fortification in the range of 5–20% improved the characteristics of chicken sausages. There was an increase in protein and fat contents and in the CIE L* value. The texture profile of the sausage improved, especially its hardness. In the sensory assessment, chicken skin fortification with the chicken sausage mixture improved the level of preference for color and flavour, especially in the T5 treatment.